An Enzymatic Domain for the Formation of Cyclic Ethers in Complex Polyketides1. Issue 50 (4th November 2013) - Pöplau, Petra; Frank, Sarah; Morinaka, Brandon I.; Piel, Jörn
<x xml:space="preserve">Abstract</x> Champion cyclist: In vitro studies on the pederin biosynthetic pathway identify pyran synthases (PS) as a new family of polyketide synthase domains that stereoselectively form diverse five‐ and six‐membered ether rings by oxa‐conjugate cyclization during carbon‐chain elongation. These domains could be useful tools for chemoenzymatic synthesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>